Reef Fish Diversity Across the Temperate South Pacific Ocean - Pérez-Matus, Alejandro; Neubauer, Philipp; Shima, Jeffrey S.; Rivadeneira, Marcelo M. (Frontiers in Ecology and Evolution, 2022)
Patterns of species richness and their structuring forces at multiple scales provide a critical context for research efforts focusing on ecology, evolution, and conservation. Diversity gradients have been demonstrated in tropical reef fish, but corresponding patterns and mechanisms remains poorly understood in temperate regions. We conducted hierarchical (spatially nested) sampling of temperate reef fish faunas across >140 degrees of longitude in eastern and western South Pacific Ocean. Our sampling efforts spanned five distinct provinces: the Southeast Australian Shelf (SAS), Northern and Southern New Zealand (N-SNZ), Juan Fernandez and Desventuradas Islands (JFD), and the Warm Temperate Southeastern Pacific (WTPA). We evaluated (i) spatial variation in patterns of species richness and abundance (using Chao 1 index), and distribution of functional diversity (using several functional attributes: max body size, trophic groups, feeding guilds, trophic level, habitat use, gregariousness and activity patterns) and ii) scale-dependencies in these patterns. Species richness declined from west to east across the temperate South Pacific, but this pattern was detectable only across larger spatial scales. A functional redundancy index was significantly higher in the western South Australian Shelf at multiple scales, revealing that species contribute in equivalent ways to an ecosystem function such that one species may substitute for another. We also detected that patterns of variation in functional diversity differed from patterns of variation in species richness, and were also dependent on the spatial scale of analysis. Lastly, we identified that species’ traits are not equally distributed among reef fish assemblages, where some provinces are characterized by a distinct functional component within their reef fish assemblages. Planktivorous and schooling species, for instance, dominated the assemblages in the eastern Pacific, which is characterized by having higher primary productivity and steep bathymetric slopes favoring these traits. Demersal and pairing behavior traits dominated the reef fish assemblages in western Pacific provinces (SAS, SNZ). We conclude that combining the identifies and species’ traits allow us to disentangle historical, biogeographic and environmental factors that structure reef fish fauna.